2019
DOI: 10.3390/ijerph16214083
|View full text |Cite
|
Sign up to set email alerts
|

Association of Working Hours and Patient Safety Competencies with Adverse Nurse Outcomes: A Cross-Sectional Study

Abstract: The environment of health organizations can determine healthcare quality and patient safety. Longer working hours can be associated with nurses’ health status and care quality, as well as work-related hazards. However, little is known about the association of hospital nurses’ working hours and patient safety competencies with adverse nurse outcomes. In this cross-sectional descriptive study, convenience sampling was employed to recruit 380 nurses from three tertiary care hospitals in South Korea. Data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 33 publications
5
31
1
Order By: Relevance
“…The findings of our study add to the growing body of literature evidencing that one of the most reported barriers nurses encounter in performing their roles is the “lack of time” due to understaffing. Several studies conducted in several countries have proved that the shortage of nurses is associated with higher mortality rates and increases adverse patients' events (Fagerstrom et al, 2018; Griffiths et al., 2019; Son et al., 2019,). The question is that, although understaffing in the nursing profession remains an issue in many countries, the quality of nursing care and the potential for poor nursing care to do patients great harm has been the focus of numerous reports in the past (Care Quality Commission, 2011; Health Service Ombudsman, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of our study add to the growing body of literature evidencing that one of the most reported barriers nurses encounter in performing their roles is the “lack of time” due to understaffing. Several studies conducted in several countries have proved that the shortage of nurses is associated with higher mortality rates and increases adverse patients' events (Fagerstrom et al, 2018; Griffiths et al., 2019; Son et al., 2019,). The question is that, although understaffing in the nursing profession remains an issue in many countries, the quality of nursing care and the potential for poor nursing care to do patients great harm has been the focus of numerous reports in the past (Care Quality Commission, 2011; Health Service Ombudsman, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with those of previous studies that linked long/irregular working hours to emotional and mental fatigue, disruptions of normal sleeping and waking hours, depression and various illnesses such as musculoskeletal disorders (Harris et al, 2015). In addition, the health and safety of the patients decreased as the nurses’ working hours (P Griffiths et al, 2014; Son et al, 2019; A. Trinkoff et al, 2011).…”
Section: Disussionmentioning
confidence: 99%
“…To work as a nurse -either as a qualified nurse or nursing aide -individuals need to be responsive and highly accountable 24/7 in order to fullfill the health service requirements (Rosa et al, 2018). Therefore, nurses need to have worked for an adequate amount of time in the health sector to be able to provide high-quality care (Rosa et al, 2018 (Son et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A problem linked with staffing issues is having to perform overtime with frequently being on call. Staff is working extended hours, which is linked to increased incident reports (Son, Lee, & Ko, 2019). Staff making errors are likely to be affected by burnout, dissatisfaction with the profession, poor quality of care, and leaving the job (Dewa, Loong, Bonato, & Trojanowski, 2017).…”
Section: Structure Issues: Human Capital and Manpowermentioning
confidence: 99%